Mérimée y Borges, ¿una posible intertextualidad? - García, Mariano (Thélème. Revista Complutense de Estudios Franceses, 2007)
Borges spoke dismissively about French literature every time he could. Some French authors, though, left their influence in the Argentine writer’s work. One of them could be Mérimée, who in his second book, La Guzla, offers a short story that might have been the germ of one of Borges most famous stories, “La intrusa”. It is our intention to determinate, from a purely textual level, using Genette’s Palimpsestes, if there is a possibility of establishing a relation between both texts and, if there it is, in what does this knowledge contributes to evaluate the originality in Borges work.